Groundwater potential and its management in the hard rock terrain: a case study from the Varada River, India - Wodeyar, B. K.; Marihal, S. S.; Gudagur, J. T. (Journal of Nepal Geological Society, 2000)
The study area occupies over 2,900 km2 in the Varada River Basin of the Haveri District, the Karnatak State, India. Residual hills, pediments, pediplains, and ridges are the major landforms. Hard rocks, viz., greywacke, biotite schist, and associated blocks of Archean age (Ranebennur-Sirsi series) constitute the country rock. The region is also crisscrossed by a number of lineaments. In this area, there are no large-scale irrigation schemes and industries. Depth to water table and quality of groundwater varies from place to place. Though most part of the region has moderate rainfall and groundwater potential, lowering in water table depth has been observed due to overdraft by excessive pumping. The zones of fresh ground water and brackish water are demarcated based on integrated geological and hydrogeological investigations. In the paper, total groundwater demand at present and for the future few years, available reserves, and scope for further development and management are discussed.